2018
DOI: 10.2147/lctt.s173724
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell to small cell lung cancer on PD-1 inhibitors: two cases on potential histologic transformation

Abstract: IntroductionHistologic transformation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) is a well-recognized mechanism of resistance in EGFR-mutant adenocarcinoma upon treatment with TKIs, but rarely reported with programmed death1 (PD-1) inhibitors. We report two cases of potential transformation during treatment with PD-1 inhibitors.Case presentationsCase 1, a 65-year-old man was diagnosed with stage IVa lung adenocarcinoma on pleural fluid cytology. He received six cycles of carboplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Recent studies revealed that transformation to small-cell carcinoma is associated with inactivation of Rb1 and p53, which may derive small-cell carcinoma clones from adenocarcinoma at a very early stage, owing to divergent evolutionary processes (10). Transformation to small-cell carcinoma has already been reported in patients treated with ICI for adenocarcinomas of the lung (11, 12). The mechanisms are believed to be similar to those of patients treated with EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies revealed that transformation to small-cell carcinoma is associated with inactivation of Rb1 and p53, which may derive small-cell carcinoma clones from adenocarcinoma at a very early stage, owing to divergent evolutionary processes (10). Transformation to small-cell carcinoma has already been reported in patients treated with ICI for adenocarcinomas of the lung (11, 12). The mechanisms are believed to be similar to those of patients treated with EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 83%
“…By any measure, the number of clinical cases of acquired resistance to ICIs reported in the literature is remarkably small. We identified 13 clinical reports comprising a total of 58 patients with acquired resistance to ICIs across all tumor types (Abdallah et al, 2018;Anagnostou et al, 2017;Ascierto et al, 2017;George et al, 2017;Gettinger et al, 2017;Hu et al, 2018;Iams et al, 2019;Kakavand et al, 2017;Koyama et al, 2016;Le et al, 2017;Sade-Feldman et al, 2017;Trujillo et al, 2019;Zaretsky et al, 2016) (Figure 2 and Table S1). Importantly, these reports use differing inclusion parameters for acquired resistance and represent a heterogeneous population.…”
Section: Clinical Data On Acquired Resistance To Icismentioning
confidence: 99%
“…Patients with advanced NSCLC who had received molecularly targeted therapies prior to small cell transformation or non-lung primary cancers were excluded. Nine patients were identified from five articles (three case series [6][7][8] and two case reports 9 10 ) and one meeting abstract (index case).…”
Section: Systematic Reviewmentioning
confidence: 99%